The Impact of the COVID-19 Pandemic on Mortality Rates From Non-Communicable Chronic Diseases in Taiwan: An Interventional Time Series Study - Chen-Mao Liao; Chen-Mao Liao; Yi-Wei Kao; Yi-Wei Kao; Chih-Ming Lin; Chih-Ming Lin; Pei-Yu Lai; Pei-Yu Lai (International Journal of Public Health)
ObjectivesTo examine whether the likelihood of death from non-communicable diseases nationwide was heightened during the COVID-19 pandemic.MethodsData on mortality caused by seven leading non-communicable chronic diseases from 2011 to 2022 were extracted from Taiwan’s Death Registry. Monthly standardized mortality rates were analyzed using an intervention time series model.ResultsThe monthly mortality rate showed a significant upward trend during the pandemic in the rate of mortality due to heart diseases, diabetes, and hypertension diseases (p < 0.001). The 2021 monthly rates of mortality caused by the three diseases showed a significant increase of 4.3%, 8.2%, and 13.4%, respectively, compared to the 2020 rates and continued until the end of the study period. No upward or downward post-intervention shift was observed for malignant tumors, renal disease, and liver diseases.ConclusionAdverse individual behaviors and reduced health services might have raised severe concerns for patients with cardiovascular diseases and diabetes. Health promotion and medical resource allocation are crucial for patients with disadvantaged health and sociodemographic factors and related metabolic conditions during the pandemic.